Seroprevalence and contributing factors of transboundary animal diseases in sheep and goats: a study in Peninsular Malaysia - Jimale, Yonis Ahmed; Jesse, Faez Firdaus Abdullah; Paul, Bura Thlama; Chung, Eric Lim Teik; Zakaria, Aida; Azhar, Nur Amira; Mohd Lila, Mohd Azmi (Springer Science and Business Media, 2024)
Diseases caused by small ruminant lentiviruses, Mycobacterium avium ssp. paratuberculosis (MAP), Schmallenberg virus, and peste des petits ruminants virus (PPR) is globally recognised as serious threats to the ruminant industry due to their potential to spread rapidly across boundaries. Despite their global distribution and negative impacts on ruminant production, there is a gap in knowledge of the current trends in their epidemiology among sheep and goat populations in Peninsular Malaysia. This study was therefore designed to fill the gap of knowledge concerning the seroprevalence and contributing factors of CAEV, paratuberculosis, SBV, and PPRV among small ruminants from selected flocks in Selangor, Negeri Sembilan, and Pahang states in Peninsular Malaysia. A cross-sectional study design was used to collect animal data and blood samples for serological assays simultaneously. The ID Screen (ID.VET, France) indirect ELISA screening tests were used to detect serum antibodies directed against CAEV/MVV (VISNAS Ver 0922), paratuberculosis (PARAS Ver 0516), SBV (SBVC Ver 1114) and PPRV (PPRC Ver 0821). There was 45.4% (95% CI = 40.74–50.74), 6.8% (95% CI = 4.66–9.69), 27.8% (95% CI = 23.35–32.77), and 2.6% (95% CI = 1.11–0.51) true seroprevalence for CAEV, paratuberculosis, SBV, and PPR, respectively. Geographical location and species were the risk factors for CAEV and paratuberculosis, while the management system and age of small ruminants were the risk factors for SBV. The present study is the first to document a large-scale seroprevalence of MAP and PPR infection among sheep and goat flocks in Peninsular Malaysia. The presence of PPRV and MAP antibodies among small ruminant flocks is signalling current or previous exposure to the pathogens or cross reactions with similar antigens. This finding further suggests the potential for future outbreaks of these devastating diseases among sheep and goats in Malaysia. The high seroprevalence of CAEV and SBV among small ruminants indicates high levels of exposure to the viruses in the environment, which is a potential threat to production.